Role of ecosystem of reservoir basin of the Dnieper river for ensuring life standards and population’s health in Ukraine - Shapar A.G. (Medičnì Perspektivi)
In this article the reasons of the environment quality deterioration, inclu¬ding its component - water are considered, as well as methods to resolve this problem are offered. High quality of life provides for high economic and social standards, including public health. The share of environmental quality impact on morbidity rate reaches 25%, while the role of water is extremely important. At present medicine does not yet have data on the interactions between different types of diseases and water chemical composition. We need to know the impact of each indicator of water quality on health and human lifespan. In Ukraine about 25 million of population, as well as industrial and agricultural enterprises meet their needs of the water at the expense of the Dnieper river basin. As a result of construction of six extra-large reservoirs they overregulated flow of the river, which led to serious contamination of the water and catastrophic consequences for the ecosystem. Proportion of shallow water constantly increases due to siltation of reservoirs. One of the major challenges is to provide population with qualitative natural water resources. Nature prompts effective solutions. For example, water passes through the natural barriers and is purified from biofouling. A widespread prohibition on discharging untreated water into reservoirs and total transition to water recycling technologies may significantly reduce chemical contamination.